Does the blunted stimulation of skeletal muscle protein synthesis by aging in response to mechanical load result from impaired ribosome biogenesis? - Chaillou, Thomas; Montiel-Rojas, Diego (Frontiers in Aging, 2023)
Age-related loss of skeletal muscle mass leads to a reduction of strength. It is likely due to an inadequate stimulation of muscle protein synthesis (MPS) in response to anabolic stimuli, such as mechanical load. Ribosome biogenesis is a major determinant of translational capacity and is essential for the control of muscle mass. This mini-review aims to put forth the hypothesis that ribosome biogenesis is impaired by aging in response to mechanical load, which could contribute to the age-related anabolic resistance and progressive muscle atrophy. Recent animal studies indicate that aging impedes muscle hypertrophic response to mechanical overload. This is associated with an impaired transcription of ribosomal DNA (rDNA) by RNA polymerase I (Pol I), a limited increase in total RNA concentration, a blunted activation of AKT/mTOR pathway, and an increased phosphorylation of AMPK. In contrast, an age-mediated impairment of ribosome biogenesis is unlikely in response to electrical stimulations. In human, the hypertrophic response to resistance exercise training is diminished with age. This is accompanied by a deficit in long-term MPS and an absence of increased total RNA concentration. The results addressing the acute response to resistance exercise suggest an impaired Pol I-mediated rDNA transcription and attenuated activation/expression of several upstream regulators of ribosome biogenesis in muscles from aged individuals. Altogether, emerging evidence indicates that impaired ribosome biogenesis could partly explain age-related anabolic resistance to mechanical load, which may ultimately contribute to progressive muscle atrophy. Future research should develop more advanced molecular tools to provide in-depth analysis of muscle ribosome biogenesis.